Maintaining the transport system under extreme weather events: a dual-network perspective - Miao, Xin; Banister, David; Tang, Yanhong; Li, Min; Xi, Bao (Technological and Economic Development of Economy, 2014)
Recent years have seen an increase in the frequency of extreme weather events globally, and these have resulted in severe impacts on the transport system. To the means by which the transport system can be maintained under extreme weather events is an emerging topic in transport studies, and this is augmented by a growing concern about climate change. This paper considers transport system as dual-network composed of an interrelated operation level and management level that has some similarities with the theory behind the Wardrop Principle. Evidence from the case study on the snow event in South China in early 2008 is used to draw the dual-network formulation to generalise the law of maintaining the transport system under extreme weather. The mathematical models of the dual-network focus on entropic dynamics in the operation network and matching control activities in the management network. Quantitative evidence is provided to prove the methodology. Interactions through the form of information communication and organisational collaboration within and between networks are highlighted. Incentive mechanisms are emphasised for achieving effective anticipation, prevention and collaboration to coping with extreme weather events. This paper contributes to a better understanding about the role of networks, collective behaviour, information interchange and inter-organisational collaboration in influencing the maintenance of transport system under extreme weather conditions.